(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article tells about the place of literature of Turkish nations in the works of the literature giant of Kazakh literature Mukhtar Auezov. Article says about significant works of M. Auezov, which he contributed in literature of Turkish nations and that Turkish literature was the main source of inspiration for him. Also, it mentions his considerable contribution in examination of Kyrgyz epos «Manas» and M. Auezov mentioned that he put down C. Aitmatov as his teacher. Whereas C. Aitmatov considered Auezov’s oeuvre as an example and legacy of his creativity.